Complex system of operation support of heat pump power supply - Чайковська, Євгенія Євстафіївна; Стефанюк, Вадим Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
Complex control provision by energy with heat pump on base of information as measure of the reflection of production and consumptions of the energy in correlation in united information